Customary Hegemony and Limited Female Agency: The Persistence of the Sangkal Tradition in Madurese Communities - Putri, Nur Fadila Maulana; Hadi, Mukhammad Nur; Masum, Ahmad (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
This article examines the persistence of the sangkal tradition within Madurese Muslim communities, exploring how customary hegemony influences women’s agency and interacts with local religious authority. The tradition is rooted in a cultural narrative that prohibits women from refusing the first marriage proposal (tako’ sangkal), with noncompliance believed to bring misfortune upon them. Although it lacks any foundation in Islamic jurisprudence (fiqh), the tradition continues to function as a powerful social norm influencing pre-marital decision-making. Employing a socio-legal approach, this field research draws on in-depth interviews with women who accepted or rejected their first proposals, as well as local religious leaders in Klompang Timur, Pamekasan. The study identifies four mechanisms that simultaneously sustain the sangkal tradition: the genealogical authority of ancestral custom, internalization of misfortune narratives, symbolic pressures tied to family honor, and limited religious literacy that enables customary norms to overshadow the principles of khiṭbah (marriage proposal) in fiqh. Women’s responses range from compliance to strategic negotiation, such as symbolic acceptance, to overt resistance through refusal or temporary self-displacement. Local religious leaders acknowledge that tako’ sangkal has no sharīʿah legitimacy and may be detrimental to women; yet, such recognition rarely materializes into public critique or reform. This article argues that the endurance of the sangkal tradition is driven not by religious legitimacy but by the hegemonic power of custom, the social production of fear, and the narrow space for women’s agency within family and community structures. [Artikel ini menelusuri kebertahanan tradisi sangkal dalam masyarakat muslim Madura dengan menelaah bagaimana hegemoni adat membentuk ruang agensi perempuan dan berinteraksi dengan otoritas keagamaan setempat. Tradisi ini bertumpu pada narasi kultural bahwa perempuan tidak diperkenankan menolak lamaran pertama (tako’ sangkal), dan ketidakpatuhan diyakini mendatangkan kemalangan baginya. Meskipun tidak memiliki dasar hukum dalam fikih Islam, tradisi ini tetap berfungsi sebagai norma sosial yang kuat dalam proses pengambilan keputusan pra-nikah. Melalui pendekatan sosio-legal, penelitian lapangan ini berbasis wawancara mendalam dengan para perempuan yang menerima dan menolak lamaran pertama serta tokoh agama di Klompang Timur, Pamekasan. Penelitian menemukan empat mekanisme yang secara simultan menopang tradisi sangkal: otoritas genealogis adat leluhur, internalisasi narasi kemalangan, tekanan simbolik terkait kehormatan keluarga, dan minimnya literasi keagamaan yang memungkinkan adat mendominasi prinsip lamaran (khiṭbah) dalam fikih Islam. Respons perempuan hadir dalam bentuk kepatuhan, strategi negosiasi seperti penerimaan simbolik, hingga resistensi terbuka melalui penolakan atau pengungsian sementara. Para tokoh agama setempat mengakui bahwa tako’ sangkal tidak memiliki legitimasi syariah dan berpotensi merugikan perempuan, tetapi pengakuan tersebut jarang berwujud dalam kritik publik sampai upaya reformasi. Artikel ini menegaskan bahwa bertahannya sangkal tidak didorong oleh legitimasi agama melainkan oleh kekuatan hegemonik adat, produksi ketakutan sosial, dan sempitnya ruang agensi perempuan di ruang keluarga dan komunitas.]